2016
DOI: 10.3171/2015.8.spine14284
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cervical discectomy and fusion in the outpatient ambulatory surgery setting compared with the inpatient hospital setting: analysis of 1000 consecutive cases

Abstract: OBJECTIVE In an era of escalating health care costs and pressure to improve efficiency and cost of care, ambulatory surgery centers (ASCs) have emerged as lower-cost options for many surgical therapies. Anterior cervical discectomy and fusion (ACDF) is one of the most prevalent spine surgeries performed, and the frequency of its performance is rapidly increasing as the aging population grows. Although ASCs offer significant cost advantages over hospital-based surgica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
128
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(132 citation statements)
references
References 20 publications
2
128
2
Order By: Relevance
“…Similar levels of improvement have already been reported for 1and 2-level ACDF in an ASC compared to the hospital. 31 The surgery and anesthesia times in this study are comparable to those reported in other outpatient cervical surgery studies. 15,16,19 As in most studies of outpatient cervical surgery, very few patients experienced AEs, needed to be readmitted, or underwent secondary surgery.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similar levels of improvement have already been reported for 1and 2-level ACDF in an ASC compared to the hospital. 31 The surgery and anesthesia times in this study are comparable to those reported in other outpatient cervical surgery studies. 15,16,19 As in most studies of outpatient cervical surgery, very few patients experienced AEs, needed to be readmitted, or underwent secondary surgery.…”
Section: Discussionsupporting
confidence: 85%
“…1,4 Surgeons have analyzed spinal surgeries performed in patient cohorts ranging in size from less than 100 to over 1000 patients. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Furthermore, the comparative safety and effectiveness of spine surgery performed on an outpatient versus inpatient basis have been evaluated for a variety of procedures: lumbar discectomy, 21,22 lumbar decompression, 23,24 lumbar interbody fusion, 25,26 anterior cervical discectomy and fusion (ACDF), [27][28][29][30][31][32] and cervical disc arthroplasty (CDA). 33 The complexity of outpatient spine surgeries has also increased from microdiscectomy and decompression, to single-level fusion and multi-level fusion using an anterior approach.…”
Section: Introductionmentioning
confidence: 99%
“…The goal of this study was to further investigate this issue, using sample sizes far greater than any previously reported in the literature. 5,[8][9] The 259,414 patients examined in this study is more than 35 times greater than the previous largest study comparing inpatient versus outpatient ACDF, which involved fewer than 7,300 patients. 5 Our results indicate that in the perioperative period for fusions of 1-2 levels, outpatient ACDF was associated with fewer perioperative complications than inpatient ACDF, most prominently with regard to paraplegia, postoperative infection, respiratory complications, acute posthemorrhagic anemia, and red blood cell transfusion requirement.…”
Section: Discussionmentioning
confidence: 94%
“…[6][7] The complications of outpatient versus inpatient ACDF have been examined sparsely in the literature, with only one study using a population-based database to examine surgical safety and quality between outpatient and inpatient ACDF. 5,[8][9] The present study was performed to examine this area utilizing the Health Care Cost and Utilization Project (HCUP) databases, the largest family of populationbased databases cited in the peer-reviewed literature.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows the flow diagram that reflects the search process. Among the 12 article, seven [16, 18, 21, 22, 24, 25, 27] were subsumed into the meta-analysis, and the other five [17, 19, 20, 23, 26] were included to present the complications of the outpatient surgery.
Fig. 1Flow diagram of the study selection which shows the number of citations identified, excluded and included in final analysis
…”
Section: Resultsmentioning
confidence: 99%